If it's not what You are looking for type in the equation solver your own equation and let us solve it.
5x-9=(-4+x)x-3
We move all terms to the left:
5x-9-((-4+x)x-3)=0
We add all the numbers together, and all the variables
5x-((x-4)x-3)-9=0
We calculate terms in parentheses: -((x-4)x-3), so:We get rid of parentheses
(x-4)x-3
We multiply parentheses
x^2-4x-3
Back to the equation:
-(x^2-4x-3)
-x^2+5x+4x+3-9=0
We add all the numbers together, and all the variables
-1x^2+9x-6=0
a = -1; b = 9; c = -6;
Δ = b2-4ac
Δ = 92-4·(-1)·(-6)
Δ = 57
The delta value is higher than zero, so the equation has two solutions
We use following formulas to calculate our solutions:$x_{1}=\frac{-b-\sqrt{\Delta}}{2a}$$x_{2}=\frac{-b+\sqrt{\Delta}}{2a}$$x_{1}=\frac{-b-\sqrt{\Delta}}{2a}=\frac{-(9)-\sqrt{57}}{2*-1}=\frac{-9-\sqrt{57}}{-2} $$x_{2}=\frac{-b+\sqrt{\Delta}}{2a}=\frac{-(9)+\sqrt{57}}{2*-1}=\frac{-9+\sqrt{57}}{-2} $
| 2x^2^6=0 | | 1.9s-15.81-18.7s=4.99-14.8s | | 5x+1°8x+10°=180 | | 45+(2k+k)=180 | | 15/20=6/y | | P(n)=3/n-1.2 | | (2x-1)(4x-1)=8 | | 8-2(x-3)=30 | | 3-11x=-11 | | (–7)(x–9)=42 | | 3^x=(78732/4) | | 2x^2+6x+10-180=0 | | x=21/13+4 | | 8c-0.7=1.8–2c | | y=2×5+14 | | 6+4x+6=40 | | 4x-(2x+14)=-4 | | 4(x-5)=2(x+3 | | 10y=15/13 | | 4)-11=-y+6 | | x+17=19-x | | x–18=27 | | 4f+f+6f=0 | | √5x+4=2x+2 | | 3)n/10-9=-10 | | 15x=−9/13 | | 5x=5-30x | | X-7-4x=0 | | (9x-6)/(x-2)=12 | | 2n+5+3n=0 | | 5x/1-6x=5 | | 2)9=b-(-2) |